A Review of Antibiotic Efficacy in COVID-19 Control - Hamidreza Hekmat; Aziz Rasooli; Zeinab Siami; Kauthar Amir Rutajengwa; Zahra Vahabi; Fatemeh Alsadat Mirzadeh (Journal of Immunology Research)
Severe acute respiratory disease is associated with chronic secondary infections that exacerbate symptoms and mortality. So far, many drugs have been introduced to treat this disease, none of which effectively control the coronavirus. Numerous studies have shown that mitochondria, as the center of cell biogenesis, are vulnerable to drugs, especially antibiotics. Antibiotics were widely prescribed during the early phase of the pandemic. We performed a literature review to assess the reasons, evidence, and practices on the use of antibiotics in coronavirus disease 2019 (COVID-19) in- and outpatients. The current research found widespread usage of antibiotics, mostly in an empirical context, among COVID-19 hospitalized patients. The effectiveness of this approach has not been established. Given the high death rate linked with secondary infections in COVID-19 patients and the developing antimicrobial resistance, further study is urgently needed to identify the most appropriate rationale for antibiotic therapy in these patients.